Hence an increase in I* leads to an increase in C. If
a =
1
/
2 then
==1
Change in C is
1 × 2 = 2
2 (a) Substitute C, I, G, X and M into the Y equation to get
Y = aY + b + I* + G* + X * − (mY + M *)
Collecting like terms gives
(1 − a + m)Y = b + I * + G* + X* − M*
so
Y =
(b) =
=−
Now a < 1 and m > 0, so 1 − a + m > 0. The
autonomous export multiplier is positive, so
an increase in X* leads to an increase in Y. The
marginal propensity to import multiplier is
negative. To see this note from part (a) that
∂Y/∂m can be written as
−
and Y
> 0 and 1 − a + m > 0.
(c) Y =
= 2100
==
and
∆X* = 10
so
∆Y =×10 =
3 If d increases by a small amount then the intercept
increases and the demand curve shifts upwards slightly.
Figure S5.2 shows that the effect is to increase the
equilibrium quantity from Q
1
to Q
2
, confirming that
∂Q/∂d > 0.
4 (a) Substituting equations (3) and (4) into (2) gives
C = a(Y − T *) + b = aY − aT* + b (7)
Substituting (5), (6) and (7) into (1) gives
Y = aY − aT * + b + I * + G*
100
3
10
3
10
3
1
1 − 0.8 + 0.1
∂Y
∂X*
120 + 100 + 300 + 150 − 40
1 − 0.8 + 0.1
Y
1 − a + m
b + I* + G* + X* − M*
(1 − a + m)
2
∂Y
∂m
1
1 − a + m
∂Y
∂X*
b + I* + G* + X* − M *
1 − a + m
1
/2
1 −
1
/2
∂C
∂I*
so that
Y =
Finally, from (7), we see that
C = a − aT* + b
=
=
(b) > 0; C increases. (c) 1520; rise of 18.
5(1)From the relations
C = aY
d
+ b
Y
d
= Y − T
T = tY + T*
we see that
C = a(Y − tY − T *) + b
Similarly,
M = m(Y − tY − T *) + M*
Substitute these together with I, G and X into the Y
equation to get the desired result.
(2) (a) =
Numerator is negative because m < a.
Denominator can be written as
(1 − a) + at + m(1 − t)
which represents the sum of three positive
numbers, so is positive. Hence the autonomous
taxation multiplier is negative.
m − a
1 − a + at + m − mt
∂Y
∂T*
a
1 − a
aI* + aG* − aT* + b
1 − a
a(−aT* + b + I* + G*) + (1 − a)(−aT* + b)
1 − a
D
F
−aT* + b + I* + G*
1 − a
A
C
−aT* + b + I* + G*
1 − a
Solutions to Problems
640
Figure S5.2
MFE_Z02.qxd 16/12/2005 10:51 Page 640